Scholarship on the margins: Biblical and secular learning in the work of Jacob of Edessa - Salvesen, A (Peeters, 2015)
Jacob of Edessa (c. 640–708 CE) is much revered in the Syrian Orthodox tradition. A noted polymath, his range covered exegesis to canon law, orthography to science. In the modern period this has tended to mean that his works are studied separately according to genre. In recent years, Jacob’s version of the Old Testament has received a good deal of attention from scholars, but its actual purpose remains a puzzle. Previous work has suggested that it was designed to replace the Peshitta as an authorized version, or was intended as an improvement on the Syrohexapla, or was an aid to appreciating biblical commentaries translated from Greek. This paper suggests an alternative solution. Taking an overview of Jacob’s life and work, it argues that his Old Testament revision may have been designed primarily for educational purposes and to advocate the study of Greek Scripture as part of the monastic curriculum.